3x - y = 0

5x + 5 = 0

3x - y = 0

5x + 5 = 0

Tutors, please sign in to answer this question.

Alexandria, VA

5x+5=0

5x+5-5=0-5

5x=-5

5x/5=-5/5

x=-1

3(-1)-y=0

-3-y=0

-3+3-y=0+3

-y=3

y=-3

Olney, MD

3x - y = 0

5x + 5 = 0

Solve for x:

5x + 5 = 0

5x = -5 [Subtract 5 from both sides]

Plug x = -1 into the first equation and solve for y:

3x - y = 0

3(-1) - y = 0 [Plugged in -1 in place of x, since x = -1]

-3 - y = 0 [Add y to both sides]

Evan F.

Mathematics graduate looking to enhance your mathematics ability.

Cambria Heights, NY

4.9
(315 ratings)

John P.

Tutor of math and physics, recent college graduate

Short Hills, NJ

5.0
(21 ratings)

- Algebra 1 4027
- Math 9714
- Algebra 5020
- Math Help 5382
- Algebra Word Problem 2462
- Word Problem 5059
- Algebra 2 Question 524
- Precalculus 1531
- Algebra Help 964
- Geometry 1873